Long-Chain Fatty Acids and Inflammatory Markers Coaccumulate in the Skeletal Muscle of Sarcopenic Old Rats. (1st July 2019) - Laurentius, Thea; Kob, Robert; Fellner, Claudia; Nourbakhsh, Mahtab; Bertsch, Thomas; Sieber, Cornel Christian; Bollheimer, Leo Cornelius
Abstract : Obesity and inflammation are reportedly associated with the pathogenesis of sarcopenia, which is characterized by age-related loss of skeletal muscle mass. Intramuscular fat deposits have been found to compromise muscle integrity; however, the relevant fat compounds and their roles as mediators of muscular inflammation are not known. The aim of this study was to identify potential correlations between inflammation markers and lipid compounds that accumulate in the quadriceps muscle of previously described Sprague-Dawley (SD) rat model for high-fat diet- (HFD-) induced muscle loss. Six-month-old SD rats were continuously fed a control (CD) or HFD until the age of 21 months. Magnetic resonance imaging (MRI) revealed a significant decline in muscle cross-sectional area in male SD rats as a result of HFD, but not in female rats. Here, we developed a new procedure to quantitatively identify and classify the fatty acid methyl esters (FAMEs) in rats' quadriceps muscles from our former study using gas chromatography-mass spectrometry (GC-MS). Fatty acid analysis revealed accumulation of octadecadienoic (linoleic acid), octadecanoic (stearic acid), and octadecenoic (vaccenic acid) acids exclusively in the quadriceps muscles of male rats. The designated fatty acids were mainly incorporated into triacylglycerols (TAGs) or free fatty acids (FFAs), and their proportions were significantly elevated by consumption of a HFD. Furthermore, the number of resident immune cells and the levels of the chemokines RANTES, MCP-1, and MIP-2 were significantly increased in quadriceps muscle tissue of HFD-fed male, but not female rats. Together, HFD-induced muscle loss in aged male SD rats is associated with greater deposits of long-chain fatty acid esters and increased levels of the inflammatory markers RANTES, MCP-1, and MIP-2 in skeletal muscle tissue. This trend is further reinforced by long-term consumption of a HFD, which may provoke synergistic crosstalk between long-chain fatty acids and inflammatory pathways in sarcopenic muscle.